Factors associated with stress among mothers of hospitalized children admitted through emergency department (Journal of Patan Academy of Health Sciences, 2019)
Introductions: Hospitalization of a child is stressful for mothers, affects child care and has long-term negative effects on both mother and child. This study aims in identify stress level and associated factors on mothers of a hospitalized child admitted through emergency department. Methods: A cross sectional analytical study was conducted in mothers of children admitted in pediatric ward through emergency department of Patan Hospital, Patan Academy of Health Sciences, Nepal, from April 2018 to February 2019. Purposive sampling was used to interview mothers using validated Nepali version Dass 21 to find out the stress level and related factors (child, hospital environment, economic burden and hospital staffs). The SPSS was used for data analysis. Results: Among 90 mothers, 42 (46.7%) showed extremely severe stress and 19 (21.1%) in severe stress. Uncertainty of future of child’s illness 72 (80%), facilities of hygienic drinking water 66 (73.3%) in hospital, cost of treatment 47 (52.2%), and inadequate explanation by nursing staffs about procedures 39 (40%) were related factors of stress. Mothers stress significantly and positively correlated with child related factor (r=0.562) and economic burden (r=0.253). Conclusions: Mothers of hospitalized children were stressed with child related factors of uncertainty of illness and economic burden of cost of treatment.